Effect of Atomic Charge and Some Physical Properties on pKa of Substituted Pyridines - Mahmmoud S. Saieed; Zaheda A. Najim (College of Education for Pure Sciences, 1970)
Abstract A number of different levels of theoretical calculations have been used for assigning the Mulliken charge to the atoms of mono-substituted pyridines, including both quantum chemical and empirical schemes. A reasonable acceptance for any successful theoretical scheme of calculation is that atomic charges produces should vary in a manner consistent with chemical intuition and more specifically, that these variation should be correlated in a sensible way with experimental observations. The Mulliken charge was calculated using six different theoretical levels (AM1, PM3, MNDO, HF, DFT, MP2). After that the Mulliken charges were tested for their ability to represent variation in the pKa values of 14 mono - substituted pyridines. In all cases the Mulliken charge at the nitrogen and the two α - carbon atoms were taken as a representative regression parameters. The Mulliken charge at nitrogen atoms calculated by AM1 and HF levels yielded the most successful correlations with pKa. Also using other theoretically calculated independent variable such as the heat of formation, leads to improve the correlation with values of pKa.